Toxicity of organophosphorus pesticides to the stingless bees Scaptotrigona bipunctata and Tetragonisca fiebrigi - Dorneles, Andressa Linhares; Rosa, Annelise de Souza [UNESP]; Blochtein, Betina (Springer, 2017)
This study estimated the toxicity of the insecticides chlorpyrifos and phosmet to the stingless bees Scaptotrigona bipunctata and Tetragonisca fiebrigi. The results showed significant differences in susceptibility between the tested species, indicating that S. bipunctata are more tolerant to chlorpyrifos than T. fiebrigi in both assays. In contrast, the two tested stingless bee species showed no significant differences in susceptibility to phosmet. Our findings indicated that the insecticides chlorpyrifos and phosmet are potentially dangerous to S. bipunctata and T. fiebrigi both topically and by ingestion. It is essential to propose measures to minimize the impact of these products on pollinators. This study is the first evaluation of the lethal effects of the insecticides chlorpyrifos and phosmet to S. bipunctata and T. fiebrigi, and it provides important support for future studies on pesticide toxicity in stingless bees.
Keywords: acute oral toxicity; acute topical toxicity; chlorpyrifos; phosmet; pollinators